Morphology of lungs of the porcupine (Hystrix cristata) - Ozdemir, D.; Ozudogru, Z.; Yilmaz, S.; Atalar, O.; Karan, M.; Dinc, G. (Taylor & Francis Ltd, 2006)
This study was carried out to investigate the structure of lungs of the porcupines. It was found that pulmo dexter and sinister consisted of five and three lobes, respectively and lobus caudalis was the largest part of both the pulmones. The upper air-conducting airways of the lung were lined by an epithelium characterized by ciliated cells among which were dispersed goblet cells. The alveolar surface was lined by squamous type I pneumocytes and cuboidal type H granular pneumocytes.
Keywords: Hystrix cristata; porcupine; epithelium; lung